Transition‐Metal Catalyzed C−H Alkylation Using Epoxides as Alkylating Reagents - Liu, Ze‐Shui; Wang, Danni; Cheng, Hong‐Gang; Zhou, Qianghui (ChemCatChem, 2024)
The alkylation of arenes is one of the most fundamental transformations in synthetic chemistry and the transition‐metal‐catalyzed direct C−H alkylation represents a straightforward and attractive approach from both atom and step‐economy perspectives. Epoxides, the smallest three‐membered saturated O‐heterocycles that can be easily prepared in racemic or enantioenriched forms, are highly useful building blocks for the synthesis of complex organic molecules. Owing to their inherent high ring‐strain, epoxides readily undergo ring‐opening reactions and have been used as alkylating reagents for C−H alkylation catalyzed by transition metals. This review summarizes recent advances in utilizing epoxides as alkylating reagents in transition‐metal‐catalyzed C−H alkylation as well as their synthetic applications in organic synthesis. This review highlights the recent advances in utilizing epoxides as alkylating reagents in transition‐metal‐catalyzed C−H alkylation, along with its associated synthetic applications in organic synthesis.